2020
DOI: 10.1016/j.xfss.2020.10.005
|View full text |Cite
|
Sign up to set email alerts
|

Stage-dependent actions of antimüllerian hormone in regulating granulosa cell proliferation and follicular function in the primate ovary

Abstract: Objective: To study the direct action and physiological role of antim€ ullerian hormone (AMH) in regulating ovarian follicular development and function in vivo in primates. Design: Animals were assigned to six treatment sequences in a crossover design study. Intraovarian infusion was performed during the follicular phase of the menstrual cycle with agents including: control vehicle; recombinant human AMH (rhAMH); and neutralizing anti-human AMH antibody (AMHAb). Before ovariectomy after the final treatment, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…In mouse experiments, researchers found that as AMH expression decreased, apoptotic granulosa cells increased, suggesting a positive correlation between AMH and the number of granulosa cells [ 18 ]. Studies have shown that AMH can increase the expression of stem cell factor/kit ligand [ 28 ] and can regulate the proliferation of granulosa cells in a phased manner to promote the growth of early follicles [ 29 ]. In addition, follicle size is the key indicator for successful follicle development [ 30 ], and ultrasound measurement of follicle size is a reliable parameter for making many clinical decisions.…”
Section: Discussionmentioning
confidence: 99%
“…In mouse experiments, researchers found that as AMH expression decreased, apoptotic granulosa cells increased, suggesting a positive correlation between AMH and the number of granulosa cells [ 18 ]. Studies have shown that AMH can increase the expression of stem cell factor/kit ligand [ 28 ] and can regulate the proliferation of granulosa cells in a phased manner to promote the growth of early follicles [ 29 ]. In addition, follicle size is the key indicator for successful follicle development [ 30 ], and ultrasound measurement of follicle size is a reliable parameter for making many clinical decisions.…”
Section: Discussionmentioning
confidence: 99%
“…For example, in female rhesus monkeys, blocking AMH action within the ovary or in cell culture inhibits preantral/small antral follicle recruitment and enhances dominant follicle selection beyond the species-typical single preovulatory follicle; conversely, enriching AMH levels under similar conditions enhances preantral/small antral follicle recruitment and impairs dominant follicle selection. 11,12 AMH-enriched monkey ovaries, not surprisingly, start to accumulate overly numerous small antral follicles with impaired selection of a dominant follicle. 12 Whether such AMH-enriched, polyfollicular monkey ovaries progress into polycystic ovaries remains to be determined.…”
Section: Loss-of-function Amh and Amhr2 Pcos Risk Genesmentioning
confidence: 99%
“…In mouse experiments, researchers found that as AMH expression decreased, apoptotic granulosa cells increased, suggesting a positive correlation between AMH and the number of granulosa cells [12]. Studies have shown that AMH can increase the expression of stem cell factor/kit ligand [20] and can regulate the proliferation of granulosa cells in a phased manner to promote the growth of early follicles [21]. In addition, follicle size is the key indicator for successful follicle development [22], and ultrasound measurement of follicle size is a reliable parameter for making many clinical decisions.…”
Section: Roc Analysismentioning
confidence: 99%